JUAL BELI ONLINE DROPSHIPPING DALAM PERSPEKTIF FIQIH MUAMALAH KONTEMPORER - Muksin, Asep (Jurnal Ekonomi Syariah Darussalam, 2024)
This research tries to uncover online buying and selling with a dropshipping system. Buying and selling online with a dropshipping system is a business selling products where the seller or dropshipper does not have to own the product to be sold. Dropshipping can also be interpreted as a buying and selling transaction system where the dropshipper can determine the price of an item that is not owned, but after receiving an order for goods from the dropshipper buyer directly buys goods from the supplier and sells them to the buyer according to the price determined by taking advantage of the difference the purchase price from the supplier with the selling price to the buyer. The dropshipping system in buying and selling online fulfills the requirements and pillars of the legality of buying and selling according to Islamic law. Buying and selling online dropshipping in its implementation is carried out with two contracts, namely the salam contract and the wakalah contract and also by modifying the consent and qabul. This conclusion is based on the author's conclusions and studies on the practice of buying and selling online with the dropshipper system. The method used in this study is a qualitative analysis method through library research with a descriptive normative approach.